2013
DOI: 10.1590/s0080-62342013000200019
|View full text |Cite
|
Sign up to set email alerts
|

Mulheres idosas: desvelando suas vivências e necessidades de cuidado

Abstract: Estudo qualitativo com abordagem da fenomenologia social que objetivou a compreensão da vivência da mulher idosa, suas necessidades de cuidado e expectativas nesse período da vida. Participaram nove mulheres, cujos depoimentos foram obtidos de fevereiro a maio de 2011, por meio de entrevista semiestruturada. A mulher idosa refere limitações de ordem física, mental e social, e valoriza a preservação de sua autonomia nas atividades diárias e no cuidado consigo mesma. Refere a família como suporte fundamental e t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
21

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 6 publications
1
2
0
21
Order By: Relevance
“…23,25 Nowadays, they take care of themselves and participate in social activities that preserve their physical and cognitive condition through activities such as dancing, travelling and crafts workshops. 22,25,26 The association found in the present study between the age group of younger elderly women and FI is not surprising. Studies have shown that women aged under 80 years are more independent.…”
Section: Discussionsupporting
confidence: 59%
“…23,25 Nowadays, they take care of themselves and participate in social activities that preserve their physical and cognitive condition through activities such as dancing, travelling and crafts workshops. 22,25,26 The association found in the present study between the age group of younger elderly women and FI is not surprising. Studies have shown that women aged under 80 years are more independent.…”
Section: Discussionsupporting
confidence: 59%
“…[3][4][5] In view of this reality, the family is the main locus of care for the elderly dependent, considering the socio-cultural, moral, and affective values, in addition to those responsible for supplying needs, such as physical space and protection, foreseen in the National Policy of the Elderly Person and in the Statute of the Elderly. [6][7][8][9] Thus, the family takes responsibility for the care of its elderly dependents and elects a family member to be the main caregiver, and may or may not produce a scenario of conflict with ethical dilemmas in the decision of the power aimed to care, 10,11 since this choice can either be an obligation or voluntary.…”
Section: Introductionmentioning
confidence: 99%
“…O aumento na expectativa de vida terá relação intrínseca com a produção do cuidado ofertado às mulheres que envelhecem. De fato, entender o fenômeno do envelhecimento e as demandas biopsicossociais vivenciadas pelas idosas facilitará a elaboração das práticas destinadas ao grupo 13 . É preciso compreender os aspectos subjetivos de modo a entender as experiências determinantes nessa etapa da vida e os cuidados necessários neste período.…”
Section: Orientações Recebidas Nos Serviços De Saúdeunclassified
“…O referencial que norteou essa investigação teve seu fundamento embasado na avaliação da atenção à saúde para a população idosa. Para tal, foram utilizadas referências que discutem: avaliação da assistência [10][11][12] , produção dos serviços de saúde 11 , práticas para as idosas nos serviços de saúde [13][14][15] , direitos legais para idosos 16 , dentre outros aspectos.…”
unclassified